Narrow-linewidth 1.5 μm quantum dot distributed feedback lasers - Becker, Annette; Sichkovskyi, Vitalii; Bjelica, Marko; Eyal, Ori; Baum, Philipp; Rippien, Anna; Schnabel, Florian; Witzigmann, Bernd; Eisenstein, Gadi; Reithmaier, Johann Peter (Proceedings of SPIE - The International Society for Optical Engineering, 2016)
The ever-growing need for higher data rates is a driving force for the implementation of higher order coherent communication formats. A key element in coherent detection is the local oscillator (LO) of the decoding unit. This device has to provide coherent light with a narrow linewidth in order to distinguish between different phase and amplitude states of the incoming signal. As predicted by theory, a drastic linewidth reduction is expected from quantum dot (QD) laser materials by the quasi zero-dimensional nature of the gain function. The impact of different gain materials consisting of different numbers of QD layers on the linewidth of distributed feedback (DFB) lasers was investigated and shows an unambiguous dependence on the layer design. Intrinsic linewidths as low as 110 kHz could be determined.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Distributed feedback laser; Linewidth enhancement factor; Optical communication; Quantum dot laser